Nutritional Management in Acute Pancreatitis - Luh Putu Listya; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2016)
Acute pancreatitis induce a catabolic stress that increase systemic inflammatory response with worsening nutritional status. Current approach in acute pancreatitis therapy was still symptomatic because of no definitive therapy yet to prevent any inflammatory and proteolytic cascade. One of the most important thing to consider in acute pancreatitis therapy was nutritional management. “Pancreatic rest” concept that formerly used have been known to increase cost, sepsis incidence due to catheter use, and also metabolic and electrolyte disorder. Nowadays, “gut rousing” concept was preferable compared to “pancreatic rest” concept, support that nutritional management was needed to stimulate and generate intestinal function. Enteral nutrition administration have to consider patient’s hemodynamic status. Necrosis incidence, respiratory failure, intensive care, and mortality was found to be lower in patients given enteral nutrition in first 48 hours compared to after 48 hours. Nutrition administration via nasogastric tube or nasojejunal tube was still in doubt while several studies showed that nasogastric tube administration was safe and tolerated, otherwise could be evaluated in larger population sample study. Nutrition and metabolic monitoring was also an important part to reach nutritional goals and reduce complications.